From point to pixel a genealogy of digital aesthetics - Hoy, Meredith (Interfaces: Studies in Visual Culture, 2017)
In this fiercely ambitious study, Meredith Anne Hoy seeks to reestablish the very definitions of digital art and aesthetics in art history. She begins by problematizing the notion of digital aesthetics, tracing the nineteenth- and twentieth-century movements that sought to break art down into its constituent elements, which in many ways predicted and paved the way for our acceptance of digital art.